Social Behavior and The Achievements of Students in Gender Perspective in SMA Negeri 1 Banjarharjo Kabupaten Brebes - Guspita, Ardhianing; Masrukhi, Masrukhi; Martitah, Martitah (Universitas Negeri Semarang, 2019)
Social inquality and learning achievements students in gender perspective. The research aim is identifying social behaviour of male students and women students, analyzing the learning achievement of students on gender perspective. A qualitative approach used with participative observation methode. Informant research was the teachers, teacher counselling and student X, XI, XII. Data collection techniques with observation, result of interviews and documentation learning students. Data analysis techniques use Harvard gender analysis include access, control, participation and benefits. The validity of data in this reserch is using triangulation techniques. Research results suggest that all students have equal occasion in a learning procession at class to achieve learning accomplishments. Behavior of boy students are more aggressive in uproar at the class, difficult to be, the informing in frequently weak in exposing the material and has low learning achievement. Teacher can develope a implementation of learning in class based on gender perspective.